Abdominal sepsis due to rupture of a giant pancreatic pseudocyst: a life-threatening complication - Arias, Francisco de Jesús Cisneros; Alfonso, Arreguín Sanchez Alejandro; Godinez Orozco, Juvenal; Martinez Rodriguez, Jesus Alexis; Jesus, Lira Martinez Alexis (International Journal of Research in Medical Sciences, 2025)
Giant pancreatic pseudocysts (>10 cm) are uncommon sequelae of severe pancreatitis and are associated with a higher risk of complications, including infection, hemorrhage, and, rarely, spontaneous rupture. This latter complication is life-threatening and requires urgent diagnosis and intervention. Although endoscopic approaches have become standard in stable patients, the role of surgical management remains pivotal in critically ill individuals. We report the case of a 22-year-old female with a history of severe acute pancreatitis and a previously drained pancreatic pseudocyst who presented with clinical signs of sepsis and acute peritonitis. Imaging revealed rupture of a large infected pseudocyst into the lesser sac with associated intra-abdominal collections. Emergency exploratory laparotomy was performed, followed by transgastric drainage and open cystogastrostomy. A comprehensive review of the current literature on diagnosis and management strategies for ruptured pseudocysts was also conducted. Intraoperative findings confirmed the presence of purulent intra-abdominal collections secondary to rupture of the giant pseudocyst. Approximately 450 ml of infected fluid was drained, and a cystogastrostomy was successfully created. The patient’s postoperative course was favorable, with resolution of sepsis, gradual recovery of gastrointestinal function, and discharge with complete clinical improvement. The review highlights the importance of early imaging-based diagnosis and the selection of appropriate intervention based on clinical severity. Spontaneous rupture of giant pancreatic pseudocysts is a rare but life-threatening event that necessitates high clinical suspicion and prompt surgical management, particularly in unstable patients. While minimally invasive techniques are first-line for selected cases, open surgical drainage remains essential for effective source control in critical scenarios. This case contributes to the limited literature on surgical resolution of ruptured pseudocysts and underscores the importance of individualized, multidisciplinary approaches in optimizing outcomes.